Fostering positive affective exercise experiences and affect-related competencies for a physically active lifestyle: The FEEL Project – Results of the Pilot-Study - Martin Robert Bührer; Stephanie Rosenstiel; Gorden Sudeck; Julia Schmid (Current Issues in Sport Science)
Introduction